Effect on Sedentarism, Sedentary Conduct and Physical Activity of a Theoretical -Practical Educational program of Physical Activity and Exercise (Revista horizonte, 2022)
Background: More than 60% of the world population does not comply with the recommended time of physical activity. Objective: To evaluate the effectiveness of a theoretical-practical educational program of physical activity and exercise on sedentary lifestyle, sedentary behavior and physical activity. Materials and methods: 26 subjects (21 women and 5 men) aged between 37 and 64 years (Average age: 48.3 years, SD: 5.9 years) formed 2 groups randomly. Physical activity level and sedentary behavior were measured through GPAQ. A program of counseling in physical activity and exercise was applied, in person and remotely for 12 weeks. Results: Sedentary behavior decreased by 16.2% (p = 0.0004) in the experimental group and 4.7% in the post-intervention control group. Increased moderate physical activity in experimental group free time by 23% (p = 0.03). Total average energy expenditure of the control group prior to the intervention was 1,197 METs / min / wk (SD: 694.7 METs / min / wk) and later 1,223 METs / min / wk (SD: 689.5 METs / min / wk ) and previous experimental group 2,395 METs / min / wk (SD: 1,138 METs / min / wk) and later 2,565 METs / min / wk (SD: 1,122 METs / min / wk), both without significant differences. Working time (vigorous and moderate), transfer and free vigor does not undergo significant changes before and after surgery (p> 0.05). Conclusion: A theoretical-practical educational program of physical activity and exercise, either face-to-face or distance learning, was effective in reducing sedentary behavior and increasing moderate physical activity in free time.